Strategi Efektif Program Literasi Informasi Perpustakaan Akademik - Setyawan, Herman; Rahayuningsih, Fr.; Diana Fauzie, Novy; Arkiyah, Nanik (Perpustakaan Universitas Gadjah Mada, 2025)
ABSTRACT Information literacy programs systematically help individuals develop skills to find, evaluate, and use information. This study analyses effective strategies in library information literacy programs in the academic environment. This research uses a mixed-method sequential explanatory; this study began with collecting quantitative data from 72 librarians at various universities in Indonesia, followed by qualitative interviews with library leaders. The results of the study show that the competence of librarians influences the success of the library information literacy program, the availability of relevant programs, and the active participation of students. This study concludes the need for continuous training for librarians, designing programs that are responsive to the needs of students, and strengthening cooperation between libraries and faculties to increase the effectiveness and participation in information literacy programs in the academic environment. This research emphasizes that developing strategic and adaptive information literacy programs can improve students' information literacy skills, support academic achievement, and strengthen the role of libraries as learning centres in universities.